Motor imagery as a tool for motor skill training in children - A. Doussoulin; L. Rehbein (Desafio Singular, 2011)
The present study aimed at checking the effectiveness of motor imagery on children's motor training. A total of 64 students aged 9 to 10 years, enrolled in three different 4th grade classes, participated in the study. Subjects in the modeling group were asked to view the video recording of an expert performing the task; those in the physical practice group were trained through the actual execution of the task; and subjects in the imagery group, were trained based solely on motor imagery. The task consisted of throwing a ball towards a target. Performance of subjects before and after training was assessed. Results showed improvements for all three groups. However, motor imagery and modeling groups obtained significantly higher mean scores than the physical practice group. Results are discussed in terms of the potential of motor imagery as a training tool in children.